Numerical Study of the Seismic Responses of Precast Segmental Column Bridge under Spatially Varying Ground Motions - Zhao, L.; Hao, Hong; Bi, Kaiming; Li, X. (American Society of Civil Engineers, 2018)
Compared with traditional monolithic columns, precast segmental columns can significantly reduce the residual displacement after a severe earthquake. Previous studies of precast segmental columns mainly focus on the column itself. Only very limited studies have investigated the seismic responses of a whole bridge structure supported by segmental columns, and all those studies assumed uniform seismic excitation at the multisupports of the bridge, although the spatial variation of earthquake loading may obviously influence the structural responses. Furthermore, the abutments can constrain the structural movement when the gap size of the expansion joint is not big enough to accommodate the relative displacement between the bridge girder and abutment, which may obviously influence the seismically induced pounding of the bridge structure. The effect of abutments on the response of bridge pounding has not yet been systematically investigated. In the present study, numerical simulations were carried out to investigate the seismically induced pounding responses of a bridge structure supported by segmental columns under spatially varying ground motions. Bridge structures without and with abutments were considered. A reference bridge with traditional monolithic columns was also analyzed. The influences of ground-motion spatial variations on the structural responses were systematically investigated. The results reveal that when abutments are not considered, the spatially varying ground excitation can dramatically change the relative pounding compared with uniform seismic loading. When abutments are considered in the numerical model, the influence of spatial variations on the bridge-pounding responses becomes less significant.